1989
DOI: 10.1083/jcb.109.1.367
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor promotes endothelial cell adhesion via an Arg-Gly-Asp-dependent mechanism.

Abstract: Abstract, Von Willebrand factor (vWF) is a constitutive and specific component of endothelial cell (EC) matrix. In this paper we show that, in vitro, vWF can induce EC adhesion and promote organization of microfilaments and adhesion plaques. In contrast, human vascular smooth muscle cells and MG63 osteosarcoma cells did not adhere and spread on vWE Using antibodies to the/3 chains of fibronectin (~) and vitronectin (~3) receptors it was found that ECs adherent to vWF show clustering of both receptors. The/3, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 48 publications
(62 reference statements)
3
54
1
2
Order By: Relevance
“…It is well known that the mature vWF promotes the adhesion of endothelial cells in an RGD-dependent fashion [7]. As clearly shown in Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…It is well known that the mature vWF promotes the adhesion of endothelial cells in an RGD-dependent fashion [7]. As clearly shown in Fig.…”
Section: Resultssupporting
confidence: 53%
“…Although these three proteins are abundant in ECM and thought to be primarily important in tissue organization under physiological conditions, there are a number of other proteins that have cell-adhesion activity in vitro and are thought to play a crucial role in more specialized stages of cellular events. [7]. A large amount of evidence is accumulating that these adhesive glycoproteins play dynamic roles in embryo-…”
mentioning
confidence: 99%
“…Importantly, VWF is an RGD-containing adhesion protein that is unique to the vascular basement membrane. 34,35 Previous studies have revealed that endothelial cells and VSMCs share a common basement membrane in mature arteries. 36,37 Because endothelial cells and VSMCs both up-regulate integrin ␣␤3, a receptor for their shared basement membrane, during angiogenesis, we considered whether VWF might regulate VSMC-dependent arterial maturation.…”
Section: Vwf Regulates Arterial Vsmc Coverage In Vivomentioning
confidence: 99%
“…In the present study, H-2-negative B78H1 and four control clones were compared to five H-2Kb transfectants, one of which (Kb-G56) showed a poor, even though interferoninducible, (Dejana et al, 1987), were routinely characterised by immunofluorescence techniques using rabbit anti-human factor VIII antigen (Behringwerke, AG, Marburg, Germany) (Balconi & Dejana, 1986;Dejana et al, 1989). The cells were cultured in medium 199 (M 199) supplemented with 20% FCS, 50 jig ml-' endothelial cell growth supplement (prepaed from bovine brain), 100 tg ml-' heparin (Sigma Chemical Co., St. Louis, MO, USA), 50 U ml-1 penicillin, 50 tg ml-' streptomycin, 2.5 tLg ml-' fungizone at 37°C.…”
Section: Methodsmentioning
confidence: 99%